Experimental Study on the Influence of AC Stray Current on the Cathodic Protection of Buried Pipe. (19th January 2016) - Ding, Qingmiao; Fan, Yueming
Abstract : The size of the damaged area of the coating and its position on the pipeline impacted the cathodic protection potential, and there was a damaged area of the greatest impact value. When damaged area was 300 mm 2, the IR drop was the largest, and this situation could easily lead to inadequate protection; when the parallel spacing between pipeline and interference source was unchanged, the measured value curves of cathodic protection potential presented "U" shaped trend with the increasing stray current interference intensity. Under certain parallel spacing between pipeline and interference source, high alternating stray current intensity would cause serious negative offsets, so that the overprotection of the pipeline occurred, and make the coating crack; there was a parallel threshold length. When less than the threshold, the pipe-ground potential increases rapidly with the parallel length increasing. In order to judge whether a pipeline was interference by AC stray current and the risk of stray current corrosion, we should make a comprehensive analysis of the cathodic protection energizing potential, the switch-off potential, AC pipe-soil potential, IR drops, and so on.